Studi Pengaruh Kinerja Keuangan terhadap Tax Avoidance - Ike Alvinurnita Tristanti; Aisyaturrahmi (Universitas Nahdlatul Ulama Surabaya, 2023)
This study aims to examine empirical evidence about the factors that influence tax avoidance. The factors used in this study are profitability, leverage, liquidity, and sales growth as independent variables. Tax avoidance is measured using the cash effective tax rate as the dependent variable. This research does not only discuss profitability, liquidity, leverage, and sales growth that affect tax avoidance. However, it also analyzes whether there are significant differences in tax avoidance in 2019 and 2020 for manufacturing companies listed on the Indonesia Stock Exchange (IDX). A sample of 58 manufacturing companies was obtained based on predetermined criteria. The analytical method used is multiple regression and paired sample t-test with the SPSS (Statistical Product and Service Solutions) application version 26. The results show that profitability in 2019 has an effect on tax avoidance, and for 2020 profitability has no effect on tax avoidance, leverage in 2019 and 2020 has no effect on tax avoidance, liquidity in 2019 and 2020 has no effect on tax avoidance, sales growth in 2019 and 2020 has no effect on tax avoidance, and there is no difference in tax avoidance in 2019 with 2020.